Wound-Healing Properties of Henna in Pilonidal Sinus Surgery: A Randomized Study - Seyed A. Khosravi; Mohammad Kamalinejad; Seyed M. Javadi; Hasan Namdar; Mohammad G. Fesharaki (Indian Journal of Dermatology)
Background: Wound complications associated with pilonidal sinus (PS) significantly contribute to its high post-operative morbidity. Therefore, speeding up the wound healing process after surgery can help minimize potential complications. This study investigated the effectiveness of Lawsonia inermis extract (LIE) in promoting wound healing following PS surgery, given its known benefits in this area. Methods: This randomized, double-blind, controlled clinical trial involved 60 patients with open post-operative PS wounds. Participants were randomly divided into three groups: the first group received LIE ointment treatment, the second group used phenytoin as a standard occlusive dressing method and the third group used eucerin ointment as a negative control. In all groups, the wound was cleansed with normal saline and dressed with wet gauze daily. A physician measured the length, depth and volume of the wounds on days 7, 14 and 28 post-PS surgery. Results: After two weeks, the LIE topical ointment significantly decreased the length and depth of the wound compared to phenytoin and eucerin ointments. Additionally, the wound volume in the LIE-treated group was substantially lower than in the other groups (P < 0.05). Conclusion: The study highlighted the wound-healing properties of henna extract. The results indicate that LIE ointment can enhance the wound healing process, thereby lowering the risk of infection and complications in post-operative wounds.